Opportunities and challenges of green logistics in Singapore - Kee, Jaclyn Chun Ling (Nanyang Technological University, 2022)
The logistics industry is deemed to be a crucial sector within the economy, however, they are also responsible for the detrimental impact on the environment. The concern over the growing impact of logistics on the environment has led to countries employing the use of green urban logistics. Thus, this report has highlighted the importance of green logistics. The case study of various countries’ green initiative provides an insight into how Singapore differs from those top countries in sustainability and from there, Singapore could take them as a reference point to improve the logistics sector within the country. Before an insight can be provided on how Singapore can improve itself, an analysis of the factors contributing to green logistics will be required to form the basis of further examination into the prospects and obstacles of green logistics in Singapore. Findings have shown that green logistics involves transportation, warehousing and packaging and this report only delves into warehousing. A warehouse is a facility that store goods for various purposes, and it is an essential component in logistics. Air pollution from the warehouse is a major problem and due to the era of e-commerce, more and larger warehouses are needed to accommodate the demand for consumer goods leading to more carbon footprint generated. This calls for the need of an eco-friendly warehouse that aims to minimise the environmental impact. Many countries including Singapore are attempting to promote the development of green buildings. However, Singapore’s initiative on such development does not show noticeable progress in meeting its goals. Qualitative and quantitative data was collated and analysed to provide a better understanding of the current progress of green warehousing in Singapore. The findings affirm that the current initiative proposed by Singapore are deemed not effective as companies are still reluctant to shift towards implementing green warehouse. The report then delves into exploring the limiting and motivating factors along with the types of challenges faced during implementation. Through the findings, it has been concluded that cost is a major limitation followed by resources and capabilities constraints as well as organizational culture. The recommendations suggested are based on the challenges faced which aim to increase the implementation rates of green measures in the warehouse. The report also covered the limitations of the recommendations and the report to provide suggestions for future works.